PLANT FIBERS: EXPLORING HANDMADE PAPER IN GHANA - Adashie, Michael; Kushiator, George; Ayim, Bertha (Penerbit Lafadz Jaya, 2023)
Handmade papermaking technology was mass accepted and considered as one of the very valuable commodities in the papermaking industry. After industrialization, handmade papers were replaced by wood pulp-based machine-made papers which destroyed the production of handmade papers. Consequently, industrialized production of paper has wrecked handmade paper production. This situation has also resulted in encouraging dependency on the importation of foreign materials in the teaching and creation of art. This presents a problem regarding sustainability especially in the area of good sources for cellulose-yielding plants that grow at fast rates due to global warming. In view of the above, the study employs a practice-based research methodology. In this exploration, twenty-two plants were collected and experimented with to test their ability to produce good sheets of paper in Ghana. The results showed an interesting array of sheets of different shades and strengths that can be used for artistic purposes. It is eco–friendly, biologically degradable, and can be recycled and affordable. It is recommended that artists, small and medium-scale enterprises, and local industries in Ghana see the value and encourage the use of handmade paper production as a traditional technology for its social, economic, and environmental benefits.